Synthesis and characterization of silk fibroin-MXene composite electrospun fibers for biomedical applications - Chengzhi Liang; Zaiwei Fan; Yudan Zhu; Yuan Cao; Jiawei Kang; Jun Tao (Frontiers in Chemistry)
IntroductionTwo-dimensional (2D) MXene, recognized for its outstanding physical and chemical properties,has gained attention as a promising material in the biomedical field. However, its potential in tissue engineering applications remains underexplored. This study focuses on synthesizing SF-MXene composite electrospun fibers and evaluating their suitability for biomedical applications.MethodsSF-MXene composite electrospun fibers were prepared through electrospinning. The fibers were characterized using field emission scanning electron microscopy (FE-SEM), Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), mechanical testing, thermogravimetric analysis (TGA), and contact angle measurements.Protein adsorption capacity and biomineralization potential were assessed. Biocompatibility was evaluated using fibroblasts (L929) and preosteoblasts (MC3T3-E1), with alkaline phosphatase (ALP) activity measured in MC3T3-E1 cells to determine osteogenic potential.ResultsThe SF-MXene composite fibers exhibited well-defined morphological and structural properties, as confirmed by FE-SEM, FTIR, XRD, and TGA analyses. Mechanical testing revealed enhanced mechanical stability. The fibers showed high protein adsorption and potential biomineralization activity. Both L929 and MC3T3-E1 cells displayed high viability on the composite fibers, with significantly increased ALP activity in MC3T3-E1 cells, indicating osteogenic potential.DiscussionThe findings demonstrate that SF-MXene composite fibers possess excellent structural, mechanical, and biological properties suitable for tissue engineering. The fibers’ ability to support cell viability, protein adsorption, and osteogenic activity highlights their potential in biomedical applications, particularly in bone tissue regeneration. These results suggest that MXene-based composites could be developed further for broader biomedical uses.